KOSAKATA PEMBUATAN KOPRA DALAM BAHASA MELAYU DIALEK PONTIANAK DI KECAMATAN SUNGAI KAKAP - Mawarni, Atika Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Copra is dried coconut pulp. This research focuses on the semantic field of analyzing data about the copra making based on the components of meaning, the definition and the meaning of each vocabularies, and the semantic function of vocabulary of copra making in Sungai Kakap District. The method used in this research is descriptive method with qualitative research form. Sources of data in this study is a speech of Malay dialect Pontianak spoken by the native speakers of Jeruju Besar village, Sungai Kakap District. Technique used in this research arelisten-involve-talk technique, record and taking note technique. Data collection tool in this research are interview, notebook and stationery, camera, and sound recorder. Based on the research conducted, researchers have collected 44 vocabularies of copra making in Malay Language Dialect Pontianak. The data consists of 21 tool vocabularies and 23 process vocabularies. Keywords: Vocabulary, Copra, Semantics.